Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1128/jvi.01473-12
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs and Unusual Small RNAs Discovered in Kaposi's Sarcoma-Associated Herpesvirus Virions

Abstract: It is widely held that any given virus uses only one type of nucleic acid for genetic information storage. However, this consensus has been challenged slightly by several recent studies showing that many RNA species are present within a range of DNA viruses that include Kaposi's sarcoma-associated herpesvirus (KSHV). RNAs extracted from purified DNA virus particles exhibit great diversity in terms of length, abundance, temporal expression, cellular localization, and coding capacity during viral infection. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
52
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 50 publications
2
52
1
Order By: Relevance
“…The three white bands observed on the sucrose gradient (Fig. 1A) were consistent with previous reports (26,36), representing the A-type (empty virus particles), B-type (intermediate virus particles), and C-type (mature virions) KSHV particles. The lower band representing the mature C-type KSHV virion particles was collected with a syringe and diluted before pelleting the virions by ultracentrifugation.…”
Section: Purification Of the Kshv Virionssupporting
confidence: 91%
See 4 more Smart Citations
“…The three white bands observed on the sucrose gradient (Fig. 1A) were consistent with previous reports (26,36), representing the A-type (empty virus particles), B-type (intermediate virus particles), and C-type (mature virions) KSHV particles. The lower band representing the mature C-type KSHV virion particles was collected with a syringe and diluted before pelleting the virions by ultracentrifugation.…”
Section: Purification Of the Kshv Virionssupporting
confidence: 91%
“…After quantifying, 10 pM concentrations of the mature library samples were used for the RNA-seq analysis. In comparison with previous reports (26,27), the transcriptome analysis with the CLC Genomic Workbench 7 software using KSHV as the reference genome detected a larger number of KSHV mRNAs in the virions. A previous DNA microarray study identified 11 KSHV mRNAs in the virions (27), but in this study, we identified more than 60 KSHV-specific transcripts, including mRNAs for latent genes ( Table 1).…”
Section: Kshv Virions Package the Viral Transcriptscontrasting
confidence: 73%
See 3 more Smart Citations